Avaliação da eficácia in vitro de diferentes aditivos antimicotoxinas através da aplicação em isotermas de adsorção e equações de dose de inclusão - Schlösser, Luara Medianeira de Lima (2025)
The thesis aims to evaluate through two studies the efficacy of the adsorptionprocessofAntimycotoxin Additives (AMAs) against aflatoxin B1 (AFB1) using isotherms andtocompare the use of isothermal models with linear regression equations in assessingtheadsorption efficacy of AMAs against deoxynivalenol (DON) and fumonisin B1 (FB1). Thus,in the first study, to determine the inclusion rate of three AMAs (AMA1, AMA2, andAMA3), were incubated in gastric (pH 3) and intestinal (pH 6) solutions at four concentrations(0.12%, 0.25%, 0.37%, and 0.5%) with 1 mg L -1 of AFB1. Subsequently, with the inclusionrate defined (0.5%), the three AMAs were incubated again at both pHs, withAFB1atconcentrations ranging from 0.05 to 4 mg L -1 . The isotherm functions were fittedtothedatausing nonlinear regression analysis, applying the Langmuir, Freundlich, and BET(Brunauer,Emmett, and Teller) models. At pH 3, AMA 1 obtained higher adsorption rates (p<0.05)compared the other AMAs. At pH 6, at concentrations of 1, 2, and 4 mg L -1 of AFB1, AMA1obtained higher adsorption results (p < 0.05) than AMA 2 and AMA 3. The Freundlichmodelprovided the best fit for the adsorption data of AMA 1, while the Langmuir model for AMA2and AMA 3. In the second study, following the same methodology as the first study, todetermine the inclusion rate of two AMAs (BBAc and SepHt), were incubatedat fourconcentrations with 1 mg L -1 of DON and 2.5 mg L -1 of FB1 separately. Subsequently, withthe inclusion rate defined (0.5%), were incubated again in solutions at pH3 andpH6, withDON and FB1 separately, at concentrations ranging from 0.5 to 10 mg L-1 . The isothermfunctions were fitted to the data using nonlinear regression analysis, applying the differentmodels for the obtained data. For both studies, the samples were incubated in an ovenat 37ºCfor 1 hour. Then, were centrifuged, diluted, and analyzed by HPLC–MS/MS. The adsorptionrates of FB1 were not different between the products tested (P > 0.05) at pH3 andpH6. ForDON, only at the concentration of 1 mg L -1 , BBAc showed better adsorption rates (P<0.05).For FB1, the Freundlich model showed the best fit at pH 3, and the Langmuir model at pH6,for both additives. For DON, the Freundlich model provided the best fit for BBAc at bothpH3 and pH 6, whereas the Langmuir model best described adsorption for SepHt at bothpH3and pH 6. All the linear regression equations showed lower R2 values comparedtotheisotherm models. Therefore, based on the two studies conducted in this thesis, it was possibleto conclude that isotherm models should be used to describe and elucidate the mycotoxinadsorption process by different antimycotoxin additives.